Ang aklatang pusa - Evasco, Eugene Y.; Yokte, Jared C. (Quezon City : CANVAS, 2018)
One midnight, there was a relentless chorus of meowing in her backyard. Ms. Salvacion was forced to come out. She looked for the source of the noise. When she approached, there they were, four kittens in a shoebox. Soon she would open a Cat Library and by so doing, she was able to help both cats and people.
Winner of CANVAS Romeo Forbes children's storywriting competition
Keywords: Children's stories, Filipino; Electronic Books